Diurnal variation in maximum endurance and maximum strength performance: A systematic review and meta-analysis - Knaier, R.; Qian, J.; Roth, R.; Infanger, D.; Notter, T.; Wang, W.; Cajochen, C.; Scheer, F. A.J. L. (Medicine & Science in Sports & Exercise, 2022)
Introduction: Diurnal variations in physical performance can affect athletes` success in competitive sports depending on whether the time of peak performance concurs with the time of competition. The purpose of this systematic review was to investigate the diurnal variation in maximum endurance and strength performance. Methods: The databases PubMed, EMBASE, and Web of Science were searched from inception to November 2020. The search string was externally reviewed according to PRESS guidelines, and the review was conducted in accordance to PRISMA guidelines and registered beforehand on PROSPERO. Eligibility criteria were that 1) the studies included humans and 2) any kind of maximum endurance or maximum strength test was performed at 3) a minimum of three different times of the day. There were no restrictions regarding study design, participants` sex, age, or fitness levels. Results: From 10,460 screened articles, 63 articles met all three inclusion criteria. Meta-analysis on the harmonizable 29 studies provided evidence for diurnal variations in physical performance. In detail, the overall effect sizes (95% confidence intervals) were 0.23 (0.05-0.40), 0.73 (0.37-1.09), 0.39 (0.18-0.60), and 0.79 (0.28-1.30) for endurance exercise tests, maximum power output in the Wingate test, handgrip strength, and jump height, respectively, all in favor of higher performance in the evening. The overall risk of bias in individual studies was moderately high. Conclusions: There is strong evidence that anaerobic power and jump height are maximal between 1300 and 2000 h. There is some evidence that handgrip strength peaks between 1400 and 2100 h, but only little evidence that there is a time of peak performance in maximum endurance.